Reaction of different cell types of the brain on neurotoxin cuprizone and hormone melatonin treatment in young and aging mice - Labunets, Irina; Rodnichenko, Anzhela; Savosko, Sergey; Pivneva, Tetyana (Frontiers in Cellular Neuroscience, 2023)
Introduction The brain myelin and neurons destruction in multiple sclerosis may be associated with the production of neuroinflammatory cells (macrophages, astrocytes, T-lymphocytes) of pro-inflammatory cytokines and free radicals. The age-associated changes of the above cells can influence on the response of nervous system cells to toxic damaging and regulatory factors of humoral/endocrine nature, in particular pineal hormone melatonin. The study aim was (1) to evaluate changes of the brain macrophages, astrocytes, T-cells, neural stem cells, neurons, and central nervous system (CNS) functioning in the neurotoxin cuprizone-treated mice of different age; and (2) to assess in such mice the effects of exogenous melatonin and possible courses of its action. Methods A toxic demyelination and neurodegeneration model was induced in 129/Sv mice aged 3–5 and 13–15 months by adding cuprizone neurotoxin to their food for 3 weeks. From the 8th day of the cuprizone treatment, melatonin was injected intraperitoneally at 6 p.m. daily, at a dose of 1 mg/kg. The brain GFPA + -cells were evaluated by immunohistochemical method, the proportion of CD11b+, CD3+CD11b+, CD3+, CD3+CD4+, CD3+CD8+, Nestin+-cells was determined via flow cytometry. Macrophage activity was evaluated by their ability to phagocytose latex beads Morphometric analysis of the brain neurons and the behavioral reactions (“open field” and rotarod tests) were performed. To assess the involvement of the bone marrow and thymus in the action of melatonin, the amount of granulocyte/macrophage colony-forming cells (GM-CFC), and blood monocytes and thymic hormone thymulin were evaluated. Results and discussion The numbers of the GFAP+-, CD3+-, CD3+CD4+, CD3+CD8+, CD11b+, CD3+CD11b+, Nestin+-cells and macrophages phagocytic latex beads and malondialdehyde (MDA) content were increased in the brain of young and aging mice under cuprizone influence. The proportion of undamaged neurons within the brain, motor, affective, and exploratory activities, and muscle tone decreased in mice of both ages. Introducing melatonin to mice of any age reduced the number of GFAP+-, CD3+- cells and their subpopulations, macrophage activation, and MDA content. At the same time, the percentage of brain neurons that were unchanged increased as the number of Nestin+ cells decreased. The behavioral responses were also improved. Besides, the number of bone marrow GM-CFC and the blood level of monocytes and thymulin increased. The effects of both neurotoxin and melatonin on the brain astrocytes, macrophages T-cells, and immune system organs as well as the structure and functioning of neurons were more pronounced in the young mice. Conclusion We have observed the involvement of the astrocytes, macrophages, T-cells, neural stem cells, and neurons in the brain reaction of mice different age after administration of neurotoxin cuprizone and melatonin. The brain cell composition reaction has the age features. The neuroprotective effects of melatonin in cuprizone-treated mice have been realized through an improvement of the brain cell composition and oxidative stress factors and functioning of bone marrow and thymus.